Harper's team : behind the scenes in the Conservative rise to power - Flanagan, Thomas, 1944- (McGill-Queen's University Press, 2009)
Harper's team fought four campaigns in five years: two leadership races and two national elections. Through trial and error - and determination - they learned to combine the Reform Party's strength in grassroots politics with the Progressive Conservative expertise in advertising and media relations, while simultaneously adopting the latest advances in information and communications technology.